1995
DOI: 10.2172/95218
|View full text |Cite
|
Sign up to set email alerts
|

A laser scanner for imaging fluorophore labeled molecules in electrophoretic gels

Abstract: A laser scanner for imaging electrophoretic gels was constructed and tested. The scanner incorporates a green helium-neon (HeNe) laser (543.5nm wavelength) and can achieve a spatial resolution of 1 9~. The instrument can function in two modes : "snap-shot" and "finish-line". In snapshot mode, all samples are electrophoresed for the same time and the gel is scanned after completion of electrophoresis, while in finish-line mode, fluorophore labeled samples are electrophoresed for a constant distance and the imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…3 using the same charge-coupled device imaging system used in Ref. (5) and found that of the resolving power provided by finish-line imaging compared to that of snapshot imaging continues to im-resolving power was lower than that obtained with our laser scanner in either mode (18). This difference in prove for all of the molecular lengths that we studied, the absolute values of resolving power for each method resolving power is not due to any inherent deficiency in the optics of the charge-coupled device system, howpeak between 2 and 3 kbp and decline thereafter.…”
Section: Finish-line Imagingmentioning
confidence: 71%
“…3 using the same charge-coupled device imaging system used in Ref. (5) and found that of the resolving power provided by finish-line imaging compared to that of snapshot imaging continues to im-resolving power was lower than that obtained with our laser scanner in either mode (18). This difference in prove for all of the molecular lengths that we studied, the absolute values of resolving power for each method resolving power is not due to any inherent deficiency in the optics of the charge-coupled device system, howpeak between 2 and 3 kbp and decline thereafter.…”
Section: Finish-line Imagingmentioning
confidence: 71%